Proposed OEIC receiver using MESFET photodetector - Chakrabarti P.; Rajamani V. (My University, 2025)
An optical receiver configuration based on the concept of using a single optically gated metal-semiconductor-field-effect transistor (MESFET) to perform the function of a photodetector and preamplifier has been introduced. The proposed optoelectronic integrated circuit (OEIC) receiver has been analyzed theoretically. A simplified noise model of the receiver has also been developed. Results have been presented for an OEIC receiver based on InGaAs MESFET supposed to be fabricated with matured InGaAs/InP MMIC technology. Theoretical results based on a simplistic noise model reveal that the proposed OEIC receiver has superior performance characteristics over the existing optical receivers.